MIRERC081/2025: ASSESSMENT OF TUBERCULOSIS PROPHYLACTIC PROGRAM UPTAKE AMONG HEALTHCARE WORKERS AT MERU TEACHING AND REFERRAL HOSPITAL: TUBERCULOSIS PROPHYLACTIC PROGRAM UPTAKE AMONG HEALTHCARE WORKERS - KINYA, LILIAN; Rutto, Dr Jane; Kithuri, Dr.Elias (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Tuberculosis remains a major occupational hazard for healthcare workers, especially in high-burden areas like Meru County, Kenya, where 4,257 TB cases were reported in 2023. Despite the proven effectiveness of Tuberculosis Preventive Therapy (TPT) in lowering the risk of developing active TB by 60% to 90%, its uptake among healthcare personnel in the county is alarmingly low, with only 2.1% of TPT recipients being healthcare workers This study aims to investigate TPT uptake among HCWs at Meru Teaching and Referral Hospital, a key Level 5 healthcare facility. The specific objectives are to: describe the demographic profile of HCWs receiving TPT, assess their adherence to the therapy, investigate their knowledge of TPT, and identify factors hindering its uptake. A cross-sectional survey design will be employed, using structured questionnaires to collect data. The analysis will be performed using SPSS, applying descriptive statistics, and results will be illustrated through charts, tables, and graphs. The insights gained will inform targeted strategies to boost TPT adherence, enhance training efforts, mitigate barriers such as stigma and limited resources, and reinforce TB prevention policies—ultimately contributing to the reduction of occupational TB and advancing Kenya’s goal of eliminating the disease.